Miss Belgium, Coca-Cola and Flemish carwashes : Mapping discourses on ‘multilingualism’ by the Dutch- and French-medium written press in Belgium - Vierendeels, Ilias; Mettewie, Laurence; Vogl, Ulrike (Dutch Journal of Applied Linguistics, 2022)
This article explores recent (1995-2018) discourses on ‘multilingualism’ in the Dutch- and French-medium written press in Belgium: how is the notion of ‘multilingualism’ thematised and evaluated and how does this reflect underlying historical, political and socio-economic sensitivities linked to the long-standing Belgian conflict? Based on a corpus of 1710 news articles and using Ruíz’ (1984) language orientations as heuristics for quantitative and qualitative analyses, the study aims to provide objectification and reflexivity over an emotional, versatile and multi-layered language-ideological debate. Similar to (inter)national tendencies indicated in previous studies, our results generally reveal attention for and a positive bias towards (prestigious) multilingualism, mainly linked to discourses of economic utility and plurality. Differences between the Dutch- and French-medium corpus, as well as recurring argumentative patterns in both corpora, however, can be traced back to ideological sensitivities of the Belgian conflict and point to the imperative historicity of Belgian language debates.